PULMONARY FUNCTION TESTS IN CHRONIC OBSTRUCTIVE PULMONARY DISEASE WITH AND WITHOUT CARDIAC FAILURE - Zardari, Mevo Khan; Sahto, Mir Muhammad; Ahmed, Syed Tousif; Rahu, AH Akbar; Badar, Ahmed (Journal of Ayub Medical College Abbottabad, 1999)
A total of 95 mate subjects were included during the course of present study. 35 COPD without cardiac failure and 30 COPD with cardiac failure. Expiratory spirometry was performed on S- model vitalograph spirometer. Vital capacity (VC), forced vital capacity (VC), forced expiratory volume one second ( F E V I expiratory ratio (FEV/FVC%) and forced expiratory flow 25-75% ( F E F 25-75%) were performed on all subjects. The ventilatory functions of the male adult control of relevant age subgroups were found to decline with advancing age. Pulmonary function tests in COPD without and with cardiac failure were significantly decreased (p<0.001) when compared with controls. In the COPD without and with cardiac failure, the difference was statistically insignificant, h was even slightly higher in COPD with cardiac failure subjects except FEF 25-75%. These tests are therefore valuable for early diagnosis in COPD subjects but in COPD with cardiac failure their correlation with severity of lung disease is not perfect.